Analysis of Science Literacy Aspects of High School Biology Textbooks: Especially on Endocrine System Material - Holila, Nur; Manalu, Kartika (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Biology lessons for class Learning carried out by teachers to students is considered important because it is in accordance with the concepts, ideas and processes that must carry out the implementation of a plan that has been prepared carefully and in detail. This research aims to analyze 2 textbooks used in carrying out learning, including: 1) books Biology for SMA/MA Class XI by Djubaedah and Purnami with publisher Grafindo Media Pratama; 2) Biology book for SMA/M A Class XI by Irnaningtyas and Istiadi with publisher Erlangga. This research uses qualitative methods with data analysis in this research using descriptive statistics. The scientific literacy analysis is intended to determine the level of scientific literacy in class XI biology textbooks. Analysis was carried out by calculating the percentage of scientific literacy in each book analyzed. This research has the results that the level of scientific literacy in class XI high school biology textbooks on endocrine material used at MAPN 4 Medan is quite good according to the assessment criteria. The scientific literacy that often appears in the analyzed biology textbooks is science as a body of knowledge, followed by science as a way of investigation, science as a way of thinking and science and its interaction with technology and society